Technological opportunity, regulatory uncertainty, and the economics of Bt Cotton in Pakistan - Spielman, David J.; Nazli, Hina; Ma, Xingliang; Zambrano, Patricia; Zaidi, Fatima (International Food Policy Research Institute, 2014)
This paper aims to shed new light on Bt cotton in Pakistan. First, the paper explores the technological, economic, and institutional aspects to Bt cotton, the history of its introduction in Pakistan, and the controversy that has accompanied its adoption during the past decade. Second, the paper characterizes cotton-producing households across several dimensions using household survey data collected in 2012. Third, the paper examines areas for further policy-relevant research that could improve the capacity of cotton-producing households in Pakistan to realize greater benefits from Bt cotton cultivation.